Violência de gênero: uma análise a partir do centro de referência para mulheres vítimas de violência – Patrícia Esber - Lazzari, Kellen Cristina Varisco (2014)
This research aims to understand the cycle of violence against women, looking specifically at women who use the services of the Center of Reference for Women Victims of Violence (CRM) in Canoas, RS. Firstly, how the center was set up and its connection to the service network in relation to violence against women in general was investigated. Secondly, it was deemed vital to analyze the violent experiences, which produce painful memories felt by the service users, in order to understand how these might help to break the cycle of violence. Finally, how service users interact and use the support provided by CRM, including their resistance strategies were considered. Theoretical references included gender in a relational perspective, gender violence, public policies aimed at women in situations of violence and social memory. As a qualitative study, participant observations and interviews with both service users and staff were done. From this empirical material, a thematic content analysis was possible. The categories that emerged were: “violence since the beginning of the relationship”, “cycle of violence”, “resistance and disruption” and “mistrust in the system”. Included in the results of this research, is the all too common belief by battered women that they hope their partner will change his ways and no longer be violent, also mistrust of the police and legal system. These two factors make it increasingly difficult to break the cycle of violence. Finally, as this research is part of a professional master program, a booklet on gender violence was produced, intending to be a device of reflection and encouragement to all women who are going through similar situation to those investigated.